Proposta de solução de problemas de scheduling considerando possibilidade de terceirização usando a técnica de otimização por colônia de formigas - Tavares Neto, Roberto Fernandes (2010)
Althought the scheduling-related literature has a high level of diversity, just a small group have been considering the possibility of outsource a set of tasks. During a literature review, only two papers related to this theme were found, both dealing on scheduling projects with outsource possibilities on single-machine environments. Along with this scenario, it was possible to stablish the ACO (Ant Colony Optimization) algorithm as a promissing tecnique to solve combinatorial problems, including scheduling problems. This thesis approaches two scheduling problems with outsourcing allowed: (i) a scheduling problem in single machine manufacturing environment and (ii) a scheduling problem in a flowshop environment. For each problem, a new ACO algorithm is proposed and implemented. To verify the quality of the results, are also proposed and implemented: (i) a mathemetical programming model for the single machine environment problem; (ii) a branch and bound algorithm for the single machine environment problem and (iii) a a mathemetical programming model for the flowshop environment problem. The results shown that both ACO algorithms generate close-to-optimal results in a shorter computational time. In the case of the single machine environment problem, the presented results are best than the results related on the literature.